The Cataract Extraction and Driving Ability Research Study Protocol: characterisation of deficits in driving performance and self-regulation among older drivers with bilateral cataract. - Meuleners, Lynn; Agramunt, Seraina; Ng, J.; Morlet, N.; Keay, L.; McCluskey, P.; Young, M. (2015)
PURPOSE: Cataract is one of the leading causes of visual impairment in Australia. As more older adults are driving, the number of people with cataract on the roads will increase. A greater understanding of the effects of cataract and cataract surgery on driving performance and driver self-regulation is essential to improve road safety. This proposed study will examine the effects of bilateral cataract surgery on driving outcomes including driving performance and driver self-regulation. METHODS: A 3-year prospective study will be undertaken in Western Australia (WA) and New South Wales (NSW). Three hundred participants (n=150 from WA and n=150 from NSW) aged >60 years with bilateral cataract will be assessed at three time points: the month before first-eye cataract surgery, 1-3 months after first-eye cataract surgery and 3 months after second-eye cataract surgery. Driving performance will be assessed using a driving simulator and driver self-regulation patterns measured using in-vehicle driver-monitoring devices. Objective visual measures, quality of life and self-reported driving difficulties will also be collected at the three assessments. CONCLUSIONS: The study results may impact on ophthalmology, optometry and general medical practices in terms of the driving advice provided to patients with bilateral cataract and those undergoing cataract surgery. The information gained from this study will allow these professionals to advise patients about specific driving difficulties they may face at different stages of cataract surgery and appropriate self-regulation practices. The results will be of use to licensing authorities in the assessment of 'fitness to drive'.